Mechanism of Strength Degradation of Fiber-Reinforced Soil Under Freeze–Thaw Conditions - Xiaojuan Yu; Xingyu Wu; Peng Zhu; Chao Liu; Chengchun Qiu; Zhongbing Cai (Buildings)
Understanding the mechanism of strength degradation in fiber-reinforced soils under freeze–thaw conditions is critical for expanding their engineering applications. In this study, shear tests were conducted on fiber-reinforced soil subjected to 0, 1, 5, 10, 20, and 30 freeze–thaw cycles to investigate variations in shear strength. The mechanisms driving these variations were analyzed through soil shear tests, fiber tensile tests, and fiber pull-out tests, all conducted under identical freeze–thaw conditions. The results indicated that fiber inclusion significantly enhances the shear strength of soils exposed to freeze–thaw cycles. However, the shear strength decreases exponentially as the number of cycles increases. The strength of fiber-reinforced soil is primarily due to the soil strength, fiber strength, and strength of the fiber–soil interface. All three components exhibit an exponential reduction under freeze–thaw conditions, contributing to the overall exponential decrease in the strength of fiber-reinforced soil.